Автоматизация деятельности страхового агента - Ляскин, Борис Александрович (Инноватика - 2019 : сборник материалов XV Международной школы-конференции студентов, аспирантов и молодых ученых, 25-27 апреля 2019 г., г. Томск, Россия)
The automation system of the insurance agent was developed. The client part of the web-application was created with the use of Angular 6. The web-application can be used by insurance agent to manage their work activities.